Evaluation of factors that influence the food consumption of patients in a hospital in Londrina, Paraná - Venancio, Camila Cunha; Carvalho, Izadora de Jesus; Nigro, Thanise Pitelli de (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Nutrição, 2022)
Hospital nutrition is important to recovery of patients, including a significant reduction in their hospitalization period, and eating is part of each patient's individualized treatment. This study aimed to evaluate the factors that influence the acceptability of meals offered by hospitalized patients. For this purpose,questionnaires on temperature, delivery time, consistency, core combination, meal presentation and taste were applied to 25 members hospitalized for more than four days, men and women, aged between 18 and 50 years. The recorded data were tabulated in an Excel 2013 spreadsheet for analysis and elaboration of tables and graphs. It was found that most patients were satisfied with the majority of the indicators. However, 68% of patients consume food brought from outside the hospital, and 31.25% consume soft drinks and fats. As for a grade for evaluation of the hospital food service recorded an average of 8.38 ± 1.69. Overall, the nutrition service of the hospital where the study was conducted exhibited a good level of satisfaction, but it should be considered that patients feel captive in the hospital environment, with fear of expressing their opinions regarding improvements in services.